Cotrimoxazole prophylaxis reduces mortality in human immunodeficiency virus-positive tuberculosis patients in Karonga District, Malawi - Mwaungulu Frank B.D; Floyd Sian; Crampin Amelia C.; Kasimba Simplex; Malema Simon; Kanyongoloka Huxley; Harries Anthony D.; Glynn Judith R.; Fine Paul E.M (The World Health Organization, 2004)
OBJECTIVE: To estimate the impact of cotrimoxazole prophylaxis on the survival of human immunodeficiency virus (HIV)-positive tuberculosis (TB) patients. METHODS: A cohort study with a historical comparison group was conducted. End-of-treatment outcomes and 18-month survival were compared between TB patients registered in 1999 and patients registered in 2000 in Karonga District, Malawi. Case ascertainment, treatment and outpatient follow-up were identical in the two years except that in 2000 cotrimoxazole prophylaxis was offered to HIV-positive patients in addition to routine care. The prophylaxis was provided from the time a patient was identified as HIV-positive until 12 months after registration. Analyses were carried out on an intention-to-treat basis for all TB patients, and also separately by HIV status, TB type and certainty of diagnosis. FINDINGS: 355 and 362 TB patients were registered in 1999 and 2000, respectively; 70% were HIV-positive. The overall case fatality rate fell from 37% to 29%, i.e. for every 12.5 TB patients treated, one death was averted. Case fatality rates were unchanged between the two years in HIV-negative patients, but fell in HIV-positive patients from 43% to 24%. The improved survival became apparent after the first 2 months and was maintained beyond the end of treatment. The improvement was most marked in patients with smear-positive TB and others with confirmed TB diagnoses. CONCLUSION: Survival of HIV-positive TB patients improved dramatically with the addition of cotrimoxazole prophylaxis to the treatment regimen. The improvement can be attributed to cotrimoxazole because other factors were unchanged and the survival of HIV-negative patients was not improved. Cotrimoxazole prophylaxis should therefore be added to the routine care of HIV-positive TB patients.